Thyroid Hormone Status in Children Taking Antiepileptic Drugs (AEDs): An Experience in a Tertiary Care Hospital of Bangladesh. - Sarker, Shyamal; Saha, Narayan; Mistry, Banita; Begum, Shameem Ara; Saha, Dipa; Hoque , Sk Azimul (Bangladesh Journal of Child Health, 2024)
Introduction: Antiepileptic drugs (AEDs) may alter thyroid hormone homeostasis at the level of biosynthesis, release, transport, metabolism and excretion of thyroid hormones. The purpose of the study was to see the thyroid hormone status in children with epilepsy treating with common antiepileptic drugs. Materials & Method: The cross-sectional study was carried out in department of pediatric neurology, National Institute of Neurosciences and Hospital (NINS), Dhaka. One hundred and sixty epileptic children aged 1 year to 14 years who were on monotherapy or polytherapy with the most commonly used Antiepileptic drugs (AEDs) for at least 6 months or more were enrolled. Serum TSH and FT4 were measured in all selected patients with early morning serum sample. Result: Nearly one third of study subjects had thyroid dysfunction, most of which were Subclinical hypothyroidism (SCH). The frequency of SCH was 29.2% in carbamazepine(CBZ), 50% in oxcabazepine (OXC), 28.6% in phenobarbitone(PHB) and 13% in valproic acid (VPA) treated epileptic children. No child was found to have subclinical hypothyroidism with topiramate and ethosuximide monotherapy. Antiepileptic drugs (AEDs) monotherapy or polytherapy had no significant difference in alteration on thyroid hormone level. Use of CBZ for long duration significantly altered thyroid function. Doses of Antiepileptic drugs (AEDs) didn’t show any significant thyroid dysfunction. Conclusion: Commonly used Antiepileptic drugs (AEDs) in children with epilepsy were associated with alteration of thyroid hormones, most commonly subclinical hypothyroidism. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 58-64